(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The development of electric vehicles (EVs) has been a major driver of the automotive market’s expansion during the last 10 years. One of the major factors affecting the growth of electric cars is the infrastructure for battery charging. When an electric car’s battery is charged via the power grid, the system has to use more energy. In light of this, the researchers’ proposal calls for an off-board EV battery charging system that uses a photovoltaic (PV) array-based controller. To ensure that the electric vehicle’s battery is continuously charged, a secondary battery bank is used in addition to the PV array. The proposed system’s sepic converter and three-phase bidirectional DC-DC converter enable night or day charging of the EV battery. Both the backup battery and the EV battery are charged during the warmest portion of the day. The backup battery helps recharge the EV battery at night or on overcast days. This is the result of a Simulink simulation run in MATLAB using the suggested charge system as its basis.